Pollution : problems & solutions - National Wildlife Federation (Philadelphia : Chelsea House, 1999)
Text and activities introduce pollution, its causes and effects, and ways to prevent it.
Includes bibliographical references (p. 106-108) and index.
Science Books & Films (A.A.A.S.).
Professional
Keywords: Pollution -- Study and teaching (Elementary) -- Activity programs; Pollution -- Study and teaching